2019
DOI: 10.1186/s13027-019-0240-y
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the burden of illness related to genital warts in the Philippines: a nationally representative cross-sectional study

Abstract: Background This study estimated genital warts prevalence, genital-warts-related healthcare resource use and costs, and self-reported human-papillomavirus-related psychosocial impact among male and female patients aged 18–60 years in the Philippines. Methods Prevalence was estimated using daily logs numbering genital warts patients treated by participating physicians in 4 Philippine regions over a 5-week period (09JUL2011-24SEP2012). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
0
8
0
1
Order By: Relevance
“…A body of research shows that in 60% of cases, a single sexual contact via skin and oral mucosa can transmit the disease to the sex partner [ 8 ]. The related literature show that about 6.2 million new types of GWs occur annually in the 14–44-year-old population [ 9 ]. The findings on the prevalence of GWs in different countries have been quite divergent.…”
Section: Introductionmentioning
confidence: 99%
“…A body of research shows that in 60% of cases, a single sexual contact via skin and oral mucosa can transmit the disease to the sex partner [ 8 ]. The related literature show that about 6.2 million new types of GWs occur annually in the 14–44-year-old population [ 9 ]. The findings on the prevalence of GWs in different countries have been quite divergent.…”
Section: Introductionmentioning
confidence: 99%
“…However, we note that previous studies of the HCRU and costs associated with warts in other countries have used expert opinion as a data source. 16,17 In addition, the results reported here are from a panel of 15 oncologists, gynecologists, and dermatologists so the results may not be representative of trends observed in the entire country. Second, this study did not calculate the actual economic burden of HPV-related diseases in Algeria but rather estimated the costs based on the answers to the questionnaire plus local cost data.…”
Section: Discussionmentioning
confidence: 88%
“…14 Several publications thereafter confirm this range. [15][16][17] The total estimated cost per patient with genital warts in Algeria (diagnosis, first-and second-line treatment, and recurrence combined) was 40 825 DZD, which is equivalent to US $308 (using an online currency converter on April 13, 2021). The systematic review mentioned above reported a range of costs per episode of genital warts in different countries, from $168 to $1196 (in 2009 US dollars).…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 24 ] This highlights the need for tailoring and piloting specific HPV messages for women to minimize their adverse emotional reactions. [ 25 ] Senkomago and Saraiya (2017) stated that perceptions or behaviors including compliance with follow-up procedures, and also methods to educate or communicate with women and healthcare providers about HPV are the issues that need to be considered properly. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%